Analysis of pH Changes at the Wastewater Treatment Plant After Addition of Ultilox Effluent: Analisis Perubahan pH pada Instalasi Pengolahan Air Limbah Setelah Penambahan Limbah Ultilox - Intan Maria Novia Dorty Hulu; Aussie Amalia (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
pH is one of the indicators that determines the quality of wastewater that can affect the wastewater treatment process. Changes in pH in water greatly affect the physical, chemical, and biological processes of organisms living in it. This study was conducted to analyze the pH quality of water in the PT Coronet Crown Wastewater Treatment Plant (IPAL), before and after the addition of ultilox waste, with the addition of coagulant as an indicator that can maintain the pH of the water. Monitoring was carried out for one month after the addition of ultilox waste, namely from October 7 to November 7, 2024. The parameters measured included changes in the pH of wastewater from day to day. The pH quality standard used is in accordance with applicable regulations, namely 6-9. The measurement results showed that the pH of wastewater in the IPAL before the addition of ultilox was 7.2, but after the addition of ultilox, the pH changed to 6.5. The data shows that the pH before, during the addition, and after the addition of ultilox waste still meets the quality standards in the range of 6-9.